A POLITENESS STRATEGIES IN SPEECH ACTS OF DIRECTIVES IN A MOVIE ENTITLED “PRINCESS DIARIES” BY GARY MARSHALL. - rahma ilyas (Jurnal Educatio, 2016)
A POLITENESS STRATEGIES IN SPEECH ACTS OF DIRECTIVES IN A MOVIE ENTITLED “PRINCESS DIARIES” BY GARY MARSHALL.Rahma Ilyas, S.S, M.HumUNIVERSITAS MAJALENGKA  ABSTRACT The research conducts a research of politeness strategies used in the movie entitled “Princess Diaries” by Gary Marshall. This movie tells about a freak girl, Mia, Who surprisingly knows that she is a princess. Therefore, her grandma, Queen Clarisse, has to teach her how to act and speak in front of people or in other word how to behave politely. Consequently, there are varieties of politeness strategies used in the movies. Based on the research background above, the major problem of the researchis to study Politeness strategies in the movie “Princess Diaries” This problem is then separated into:What kinds of politeness strategy are exploited by the characters in “Princess Diaries, How is the politeness strategy employed by the characters in “Princess Diaries, Why is the politeness strategy chosen by the characters in “Princess Diaries”?Finally, dimension of sociolinguistics will be used to describe the speaker’s reason in using certain politeness strategy.From the movie, 71 data containing variety of politeness strategies are found and they are transcribed into 33 dialogues. From the total data, 10 data are taken to be analyzed based on the consideration of form, social dimension, tone and domain. Since a dialogue can contain more than one politeness strategy, the data are transcribed into 10 dialogues. The researcher finds Five types of politeness strategies in the movie. They are bald on record, positive politeness, negative politeness, off record and say nothing strategy.     This research can also be dug up more by adding the analysis of different address from in the politeness strategy. Nevertheless, there are many areas of the Politeness strategies which have not been studied yet. Keywords: directivesspeech acts, strategy, accuracy, acceptability, readability.